Blended learning as a method to improve vocabulary in online english teaching - Gonzabay Dominguez, Julio Adrian (2023)
This research work analyzed the hybrid study method: Blended Learning during the Covid-19 pandemic in English in the province of Santa Elena. The objective of this research was to recognize the results of the learning environment with this new system that was covered nationally, this analysis was highlighted for having in its context coherent, systematic, and critical thoughts. The design of this research work is qualitative, and all the information was obtained from nationally and internationally recognized scientifically. According to the results obtained from the interview with teachers who worked with this system, students adapted to the system favorably, but the only difficulty they had was the internet connection, they mentioned that Blended Learning provides tools that work in the study system because all activities are worked on during the class time. The research provides a general approach to how this learning method was initiated and how favorable it was during the pandemic.